Analysis of Transient HTRB Leakage in a SiC Field Ring Termination - Potera, R. R.; Witt, T.; Zheng, Y. (IEEE International Reliability Physics Symposium proceedings, 2020)
SiC devices operate at 8x higher electric fields than Silicon devices, which subjects the passivation layers of SiC devices to these higher electric fields during voltage blocking states. We report a novel bimodal transient variation of reverse-biased leakage current at elevated temperature in a SiC JBS diode with field ring edge-termination, the magnitude of which is sensitive to blocking voltage and temperature. Two models were hypothesized and tested, including field-inversion of the termination, and charge polarization and diffusion in the passivation dielectric which induces impact ionization without avalanche breakdown. Root cause was identified as excessive charge in the field oxide covering the termination region, and it was isolated to a process step that subjected the passivation to plasma etch. Eliminating this process step removed the bimodal transient leakage. This heightened sensitivity of terminations in wide bandgap devices to passivation charges calls for termination designs with improved robustness against process-induced charge variation in passivation.